FINANCIAL INSTRUMENTS AS AN IMPORTANT DOMINANT IN ENSURING INCLUSIVE DEVELOPMENT OF TERRITORIAL COMMUNITIES (Economic journal of Lesya Ukrainka Volyn National University, 2025)
Introduction. In the context of the latest transformational challenges, the problem of ensuring inclusive development of territorial communities is becoming increasingly relevant, and it is advisable to develop innovative approaches to the use of financial instruments in managing socio-economic development at the local level.The purpose of the article is to develop the conceptual framework for the use of financial instruments by public authorities as a means of management to ensure the inclusive development of territorial communities.Methods. The methodology of the study is based on the use of dialectical and process approaches, methods of induction and deduction, analysis and synthesis - when considering the content and specification of the essence of the concept of “inclusive development of territorial communities” and determining the imperative of this type of socio-economic development; structural and functional approach and methods of theoretical generalization, scientific abstraction, systematization, argumentation - to develop a conceptual model of the use of financial instruments as a dominant factor in ensuring inclusive development of territorial communities.Results. Based on the generalization of scientific views and the use of the process approach, the author's own definition of the concept of “inclusive development of territorial communities” is formed.The study of the key aspects of the concepts of inclusive development, barrier-free, integrated and sustainable development, and current global challenges and threats made it possible to outline the imperatives of inclusive development of territorial communities that should be taken into account by public authorities when choosing financial instruments.The use of the structural-functional approach made it possible to consider financial instruments for the inclusive development of territorial communities as a means of managing socio-economic phenomena and processes, which result in the implementation of the principles of financial policy aimed at the inclusive development of territorial communities. The article reveals the dualistic nature of the impact of financial instruments for inclusive development of territorial communities on the object of management from the standpoint of their provisioning, allocative and regulatory effects.Conclusions. Financial instruments are an important dominant of the inclusive development of territorial communities. It is through the dualistic nature of their impact on the object of management, taking into account the imperative of inclusive development, the priorities of the State regional policy and strategies for the development of territorial communities, that the goal of managing socio-economic development at the local level is achieved.
Keywords: inclusion, inclusive development of territorial communities, inclusive growth, financial instruments, barrier-free access, regional development strategy, territorial communities, management of socio-economic development.